Study on Ecotourism Development in Kapota Island Wakatobi Regency, Southeast Sulawesi Province - Wijaya, Wijaya; Damanik, Janianton (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
The current paper aims to identify the distribution of ecotourism attractions, identify the strengths, weaknesses, opportunities, and threats of ecotourism development, as well as formulate appropriate development strategies. Qualitative descriptive analysis was employed by relying on various methodologies including direct observation, unstructured interview, focus group discussion, and documentation study. It was found that Kapota Island possesses tremendous ecotourism resources and potentials due to its abundant biodiversity, such as coral reefs, mangroves, seagrass meadows, beaches, dive spots, cave, lake, landscapes, customary and traditional culture, as well as historical heritages. The island’s diversity and uniqueness remain pristine/maintained due to the support given by the Wakatobi National Park Office (Balai Taman Nasional Wakatobi – TNW), customary institutions, and local communities. Accordingly, future development strategies include: (a) integration in the development of ecotourism destinations, local island based industry, collaborative marketing through digital tourism and organization of local operators; (b) orientation towards community based ecotourism to strengthen empowerment and participation of local communities; (c) capacity building of ecotourism actors and operators (tourism awareness group, Kapota customary institution, and Village Owned Enterprise administrators); and (d) increase of collaborative capacity among stakeholders. Keywords: Conservation, Development, Ecotourism, Kapota Island